A Lost Dipinto from the Tomb of Ramesses III and New Insights into the Nature of the Architectural Feature nfr.w - Petrova, Dora.
This paper provides the editio princeps of a hieratic dipinto in corridor G of KV 11, where the Opening of the Mouth Ritual is situated. The text is of importance because it has a preserved date, which might shed more light on the question of how far the construction of the tomb proceeded during the reign of Sethnakht and depending upon whether the dipinto was written under his successor, Ramesses III. The inscription also gives insight into the nature of an architectural feature called nfr.w and how it was envisioned in the plan of the tomb. This research was carried out in the framework of The Ramesses III (KV 11) Publication and Conservation Project. doi: http://dx.doi.org/10.5913/jarce.56.2020.a010